The Relative Risk for Sports Injuries based on Pre-Participation Health Evaluation in Uganda - Lubega, Samuel K.; Timothy Makubuya (J Sports Med, 2006)
The aim of this study was to examine the relative risk of sports injuries based on preparticipation health evaluation among Uganda athletes. This prospective cohort included 546 athletes,= or> 18 years old, who were free from injury. We examined the relative risk of injuries from 4 main sports (soccer/football, n= 161, track and field, n= 106, basketball, n= 120 and rugby, n= 159) and the likelihood for sports injury based on pre-participation health evaluation (PPHE) using Pearson’s Chi square test. After a one year follow up, seventy-five lost-time injuries (n= 75) were reported. There was an increased risk of sports injuries among athletes who didn’t undergo PPHE. The relative risk (RR) for sports injuries in athletes without PPHE was greater in rugby (RR= 21.8, 95% CI, 13.6-33.88), followed by soccer/football (RR= 21.6, 95% CI, 3.1-33.78), followed by track and field (RR= 14.1, 95% CI, 9.0-23.17) and basketball (RR= 12.2, 95% CI, 7.56 to 19.63). Our chi square tests revealed that the association between injury risk among athletes exposed to injury based on their PPHE was greater and significant among athletes in track and field (X2= 23.2, p=. 01), followed by rugby (X2= 12.9, p=. 02), and basketball (X2= 10.8, p=. 02). Pre-participation health evaluation is an important risk factor in sports injury acquisition. Our findings reveal gaps in practice among personnel involved in the prevention of sports-related injuries in Uganda, thus warranting specific sports regulations.